Identification of Peptides Derived from the C-terminal Domain of Fibulin-7 Active for Endothelial Cell Adhesion and Tube Formation Disruption - de Vega, Susana (Biopolymers, 2016)
Despite the research done on pathological angiogenesis, there is still a need for the development of new therapies against angiogenesis-related diseases. Fibulin-7 (Fbln7) is a member of the extracellular matrix fibulin protein family. The Fbln7 C-terminal fragment, Fbln7-C, binds to endothelial cells and inhibits their tube formation in culture. In this study, we screened 12 synthetic peptides, covering the fibulin-globular domain of Fbln7-C, to identify active sites for endothelial cell adhesion and in vitro anti-angiogenic activity. Three peptides, fc10, fc11, and fc12, promoted Human Umbilical Vein Endothelial Cells (HUVECs) adhesion, and the morphology of HUVECs on fc10 was similar to that on Fbln7-C. EDTA and the anti-integrin β1 function-blocking antibody inhibited HUVECs adhesion to both fc10 and fc12, and heparin inhibited HUVECs adhesion to both fc11 and fc12. fc10 and fc11 inhibited HUVECs tube formation. Our results suggest that three peptides from Fbln7-C are biologically active for endothelial cell adhesion and disrupt the tube formation, suggesting a potential therapeutic use of these peptides for angiogenesis-related diseases.